Valveless pumping and mixing enhancement in acoustically featured microchannels - Wang, Shasha (2012)
The growing importance of microfluidics in life sciences and microengineering technologies leads to fast development of microfluidic devices. A generic microfluidic device can achieve many functions, among them fluid pumping and mixing are two basic functions. This thesis presents studies on a novel microfluidic chamber structure incorporated with piezoelectric actuations, which can be used for valveless micropumping and micromixing enhancement, depending on the actuation frequency. Both experimental investigation and numerical simulations are carried out to characterize the valveless micropumps and micromixers. The valveless micropump in the present study mainly consists of a nozzle-shape channel that is formed by a planar channel with an acoustic resonator profile driven by a piezoelectric disk. There are two types of the design: one has buffer areas at the inlet and outlet and the other has no buffers. Both experimental measurements and numerical simulations are conducted to investigate the pumping characteristics of these pumps. The results show that the both types of pump work well at low frequencies, in terms of relatively high pressure heads and flowrates. The pumping direction for the pump with buffers at inlet/outlet is opposite to the pump without the buffers, while the peak pumping frequencies are the same for both pumps. The peak pumping frequency is found not to be caused by the piezoelectric disk, but probably by the acoustic feature of the actuation chamber, together with the connection channels. The numerical simulations, which simplify the three-dimensional flow in the pump into a two-dimensional flow problem, are conducted by using the software FLUENT. General agreements between the experimental measurements and the simulation results are obtained, in terms of pumping flowrates, the peak pumping frequency, and the pumping directions. Besides, the simulations provide transient flow patterns inside the pumping chambers, and the results show that the net flow pumping is due to flow rectification resulted from unsymmetrical flow fields in one pumping cycle. The unsymmetrical flow patterns in the micropumps are further confirmed qualitatively by synchronized PIV measurements.